Entrepreneurship and the Extensive Margin in Export Growth : A Microeconomic Accounting of Costa Rica’s Export Growth during 1997–2007 - Lederman, Daniel; Rodríguez-Clare, Andrés; Yi Xu, Daniel (2012)
The literature on the correlation between exports and economic development runs deep into the history of economic thought and permeates policy debates. This paper studies the microeconomic structure of export growth in Costa Rica, with special emphasis on the extensive margin of trade, encompassing new exporting firms, new products, and new export markets, as well as the unit values of new versus incumbent products. The data suggest that few new firms survive the test of exporting -- more than 40 percent of firms exit export activities after one year -- and this firm turnover is associated with a steady deterioration of export unit values (prices). Furthermore, most new export products are associated with product switching by incumbent exporting firms. The typical new product introduced by incumbent firms tended to be priced at about 90 percent of the unit values of incumbent products. In contrast, the usual suspected obstacles to export growth, such as the inability of small firms to enter exporting activities or to grow their exports, appear to be important sources of export growth. In fact, the smallest exporting firms experienced the fastest growth in their export values. Some of these results are compared with those from other countries that have been examined in related literature.